Locating Tripartite Negotiations within Labour Law in Zimbabwe - Zinyama, Tawanda; Makamure, Thulani Sheila (Lighthouse: The Zimbabwe Ezekiel Guti University Journal of Law, Economics and Public Policy, 2023)
Over the past decades, lawmakers have been overhauling the welfare programme of employment security that has become a central node of attention within labour law discourse in Zimbabwe. Against this background, the purpose of this article is to bring to the fore the understanding that the respect to the rights of the workers is an integral justificatory ideal for labour law that can only become possible through tripartism. The only existing tripartite United Nations agency, the International Labour Organisation has helped to bring together governments, employers, and workers of all 187-member states to set down international accepted labour standards. Since its formation, the organisation has done a lot in achieving the goal of a decent working environment in a globalised world economy. The article demonstrates that, tripartism is not about one group or body overriding the other, it is not about superiority or who demonstrates more power than the other through the social dialogue process. It is all about open negotiations that help to advance the creation of a decent working environment that provide people a stake in lasting peace, prosperity and progress. The article highlights the importance of the interplay between the role of government and the workers and the rate to which the parties have successfully addressed the problems and solutions necessary to curb a common gap in labour law. The primary issue addressed throughout the article points to a comparative analysis on whether tripartite negotiations have yielded positive results in labour law. The article then argues that social dialogue is an instrument in promoting democracy and good governance. Therefore, tripartism becomes the most powerful tool of dealing with common labour security issues that other bodies and partners might have failed to resolve.